Traditional ecological knowledge of wild tubers used by the Orang Asli Bateq tribe on the east coast of Peninsular Malaysia - Siti Nursyadiq Anuar,; Jamilah Mohd Salim,; Dome Nikong,; Norhayati Ab Manaf,; Nur Azura Sanusi,; Khatijah Omar,; Tengku Rozaina Tengku Mohamad, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Indigenous tribes and rural communities around the world are known to rely on various plant parts for their livelihood and nutrition, most notably for food. This research aimed to examine and document the traditional ecological knowledge (TEK) of wild tuber food plants used by the Orang Asli Bateq tribe of Peninsular Malaysia. The findings of this study are critical to scientifically identify and document food sources from the forest that contribute to the tribe's livelihood and, possibly, future food security. In the Bateq villages, information was gathered via semi-structured surveys, field trips, group discussions, and key informant interviews. The results show that TEK influenced the use of wild tubers inherited from their ancestors. The Bateq ate at least 11 different types of wild tubers, including Dioscorea orbiculata, Dioscorea prainiana, and Dioscorea hispida. Most of these wild tubers are from the Dioscoreaceae plant family and must be properly processed before being consumed. The elements related to the traditional knowledge of the wild tubers are the harvesting skills and the practice in the utilization of the plant. The survey also suggests that the selection to use plant tubers is prompted by its delicious taste and nutritional value while being natural and unpolluted food. In terms of plant sustainability, the majority of the Bateq will follow certain conservation techniques to maintain the plants' availability. Understanding what underlies TEK and the tribe's practices in using wild plant resources will preserve the natural legacy of forest resources and biodiversity, and possibly contribute to future food security.